Biochemical Methane Potential (BMP) of Cattle Manure, Chicken Manure, Rice Straw, and Hornwort in Mesophilic Mono-digestion - Wijaya, Alam Surya; Jariyaboon, Rattana; Reungsang, Alissara; Kongjan, Prawit (International Journal of Integrated Engineering, 2020)
Biochemical Methane Potential (BMP) assay was used to investigate the potential of methane production from agricultural wastes and weed. The objective of the study is to investigate the methane production potential from cattle manure, chicken manure, rice straw, and hornwort (Ceratophyllum demersum). The result of the study can be used to choose the most suitable substrate for renewable energy generation as well as to prioritize waste treatment to reduce Greenhouse Gases (GHGs) emission from waste. Cattle manure (CWM), chicken manure (CHM), rice straw (RSW), and hornwort (HNW) were used as substrates for batch anaerobic digestion under mesophilic condition at 35 Â°C using 500 mL glass bottles and working volume of 350 mL with substrate at inoculum to substrate ratio (ISR) of 1:1 based on Volatile Solids (VS) weight (g VS). Parameters observed including biogas production, biogas composition, methane production, and specific methane yield. Results showed that among four substrates, RSW had the highest total biogas production of 3773.33 mL, while the lowest was CHM with 1443.00 mL. In term of the biogas composition, HNW had the highest methane proportion of 66.68% among all substrates used, while RSW had the lowest proportion (62.50%). Furthermore, the highest methane production was from RSW at 2135.52 mL and the lowest was from CHM at 736.28 mL. In addition, the highest specific methane yield was obtained from RSW with a total of 331.99 NmL CH4/g VS, while CHM had the lowest yield with 114.55 NmL CH4/g VS. From results of the study, RSW was found to be a very promising substrate for a potential source of renewable energy with a high methane yield.